2022
DOI: 10.1002/slct.202200247
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanoparticles Stabilized by Lentinan with Enhanced Peroxidase‐like Activity for Sensitive Detection of H2O2

Abstract: Natural enzymes are special proteins with excellent catalytic activity and selectivity. It is difficult to purify, store without losing the catalytic ability. Therefore, it is of great significance to study mimetic enzymes to realize the functions of natural enzymes and overcome their shortcoming. Herein, lentinan was used as a biological template to prepare palladium nanoparticles stabilized by lentinan (Pd‐LNT NPs), whose structure, activity and function were characterized. In addition, the 3,3′,5,5′‐tetrame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previous research reported that lentinan, a polysaccharide found in shiitake mushrooms, is an excellent choice as an NP stabilizer due to its remarkable solubility resulting from the abundance of hydroxyl groups [ 121 , 124 ]. In another study, lentinan was employed as a natural stabilizing agent for the formulation of NP solutions containing regorafenib, an anticancer drug with limited aqueous solubility [ 28 ].…”
Section: Stabilizers For Phytochemical-based Nps Preparation and Thei...mentioning
confidence: 99%
“…Previous research reported that lentinan, a polysaccharide found in shiitake mushrooms, is an excellent choice as an NP stabilizer due to its remarkable solubility resulting from the abundance of hydroxyl groups [ 121 , 124 ]. In another study, lentinan was employed as a natural stabilizing agent for the formulation of NP solutions containing regorafenib, an anticancer drug with limited aqueous solubility [ 28 ].…”
Section: Stabilizers For Phytochemical-based Nps Preparation and Thei...mentioning
confidence: 99%